Breast Implant Illness: A Way Forward. (March 2019) - Magnusson, Mark R.; Cooter, Rod D.; Rakhorst, Hinne; McGuire, Patricia A.; Adams, William P.; Deva, Anand K.
Abstract : Summary: The link between breast implants and systemic disease has been reported since the 1960s. Although many studies have looked at either supporting or refuting its existence, the issue still persists and has now been labeled "breast implant illness." The rise of patient advocacy and communication through social media has led to an increasing number of presentations to plastic surgeons. This article summarizes the history of breast implants and systemic disease, critically analyzes the literature (and any associated deficiencies), and suggests a way forward through systematic scientific study.